Face-to-face still-face: Comparison between interactive behaviors of full-term and preterm infants - Chiodelli, Taís (2021)
Some studies indicate differences in self-regulatory behaviors of infants, depending on their gestational age. This paper aimed to compare interactive behaviors of full-term and preterm infants in the Face-to-Face Still-Face (FFSF) paradigm. Thirty prematurely born infants and thirty full-term infants were observed in the FFSF’s experimental procedure, which consists in exposing the infant to two episodes of interaction with the mother plus another episode in which the interaction gets interrupted. The Coding System and Analysis of Infant Behaviors Expressed in Still-Face adapted was used to analyze the infants’ interactive behaviors. Significant differences were observed in self-comfort behaviors. All the infants showed the still-face and the recovery effect, and full-term infants showed a carry-over effect. Results contribute to planning interventions that will help mothers promote more positive dyadic interactions.